The impact of water conservation policies on the reallocation of agricultural water-land resources - Kavand, Hadis; Ziaee, Saman; Mardani Najafabadi, Mostafa (Frontiers in Water, 2023)
The present research explored the effects of water resources conservation policies on optimal cropping ‎pattern and farmers' profit in the Zayanderud basin using a combined hydrological-economic model ‎composed of water evaluation and planning (WEAP) and multi-objective programming (MOP) ‎models to investigate of the effects of the A2 climate change scenario with or without the ‎conservation policies. The results showed that climate change will reduce crop yields by 0.5-4%, will ‎decrease water availability by 12-19%, and will increase crop water requirements by 0-4%. It was also ‎found that the adoption of the policy of changing irrigation technology along with the policy of ‎limiting groundwater use will alleviate the effects of climate change on the farmers' profit, will ‎enhance their gross return per unit area by 5%, and will increase the economic efficiency of water use ‎from 5283 to 6002 IRR/m3. But, the policy of increasing water price cannot improve the farmers' ‎profit at the basin level and the economic efficiency of water use although it can reduce water use. ‎So, proving the improvement of profit of the farmers by applying combined water resources ‎conservation policies can play a significant role in motivating farmers to accept these policies.‎